An improved DSR energy-saving networking based on flood area limitation - Meng Jinlin (Dianzi Jishu Yingyong)
Aiming at the high networking energy consumption problem of dynamic source routing(DSR) caused by flood networking request(RREQ), a zone based route discovery mechanism(ZRDM) is proposed. ZRDM networking divides the node network area into three sub areas according to the node environment and the distribution of neighbor nodes. Each node contains a neighbor table, and the neighbor node is divided into three sub regions. At the same time, DSR networking only allows some nodes to transmit RREQ packets. Simulation results show that the proposed ZRDM networking reduces energy consumption and improves packet delivery rate. When the number of nodes is 140, compared with DSR networking, the normalized energy consumption of ZRDM networking decreases by 47.8%, and the packet delivery rate increases by about 2.78%.